(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Optimizing the density of waste materials in landfills by proper compaction prolongs the facility life due to the efficient use of landfill airspace. Cement kiln dust (CKD) is a waste by-product produced in huge amounts which exceeds the used quantities in the cement recycling industry and beneficial CKD applications. The vast amount of CKD is almost landfilled in its loose state in Egypt which causes a big loss in landfill airspace due to the low density of CKD. The hydraulic binder effect and dusty behavior of reactive CKD complicates its compaction process. Accordingly, this research was performed to investigate CKD compaction properties with three types of lubricants, which are potable water, salt water and waste oil. Maximum dry density (MDD) and optimum moisture content (OMC) for these lubricant types and different wetting methods were investigated in order to improve the landfill air space utilization and to reduce the dusty effect of CKD during compaction. The effect of immediate compaction after wetting and the effect of compaction delay by allowing CKD to hydrate initially for a certain period were studied. Compaction energy and methods of the wetting of CKD either by full submergence in water or prewetting were tested. The maximum weights of a disposed CKD and durations required to fill an intended landfill air space for different CKD conditions, lubricant types and compaction methods were presented for a case study in Ain Sokhna, Egypt.